1999
DOI: 10.1007/3-540-49162-7_6
|View full text |Cite
|
Sign up to set email alerts
|

Encrypted Message Authentication by Firewalls

Abstract: Abstract. Firewalls typically filter network traffic at several different layers. At application layer, filtering is based on various security relevant information encapsulated into protocol messages. The major obstacle for efficient verification of authenticity of messages at application layer is the difficulty of verifying digital signatures without disclosure of content protected by encryption. This is due to a traditional paradigm of generating a digital signature of a message and then encrypting the signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 24 publications
0
46
0
Order By: Relevance
“…The knowledge of the plaintext m is not required for the public verification of a message's origin. Therefore, our scheme provides the ciphertext authenticity [5] which is very useful in firewalls [24] . If required, the anonymity property is obtained by scrambling the sender's public key Y S together with the message at step 3 of Signcrypt(i.e.…”
Section: Computementioning
confidence: 99%
“…The knowledge of the plaintext m is not required for the public verification of a message's origin. Therefore, our scheme provides the ciphertext authenticity [5] which is very useful in firewalls [24] . If required, the anonymity property is obtained by scrambling the sender's public key Y S together with the message at step 3 of Signcrypt(i.e.…”
Section: Computementioning
confidence: 99%
“…For the larger part of its history, cryptography remained an art, a game of ad hoc designs and attacks [10]. Although the field retains some of this flavor, the last twenty-five years have brought in something new.…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing this security scheme from an application-oriented point of view [10], can be observed that a great amount of electronic commerce can take advantage of signcryption to provide efficient security solutions in the following areas:…”
Section: Introductionmentioning
confidence: 99%
“…Signcryption, first proposed by Zheng in 1997 [31], is a cryptographic primitive that performs digital signature and public key encryption simultaneously, at lower computational costs and communication overheads than the signature-then-encryption approach. Several efficient signcryption schemes have been proposed since 1997 [3,11,20,23,25,28]. The original scheme in [31] is based on the discrete logarithm problem but no security proof is given.…”
Section: Introductionmentioning
confidence: 99%